Trends in the Development of Human Capital in the Digitalization of the Economy - STYGUN, DINA IGOREVNA; STYGUN, ALEKSANDR VIKTOROVICH; KHUAZHEV, ASKER ASLANOVICH (The journal of contemporary issues in business and government, 2021)
The digitalization of the economy has a huge impact on all socio-economic processes in general, with globalization and the active development of innovative technologies such as blockchain, artificial intelligence and cloud services, the digital economy has become an integral characteristic of the global and national economic system. The scale of the development of the digital economy in the world is difficult to assess accurately, as of 2019, the digital economy was estimated by the Boston Consulting Group at 2,3 trillion, for a group of 20 countries it was 4.1% of total GDP, and Oxford Economics estimated digital commerce at 20,4 billion, accounting for approximately 13,8% of global sales. The growth rate of digitalization in the Russian Federation is much lower than in the United States, Japan and China, an indirect confirmation of this - the Russian Federation accounts for 1,8% of world GDP, while the productivity of supercomputers is only 0,32%, and for the development of digital economy, it is necessary to develop the national IT sector, stimulate the creation and implementation of innovative technologies in all social and economic spheres of activity, both on a national scale and at the level of the regions of the Russian Federation. The main idea of the development strategy focused on the implementation of the digital economy is the advanced formation of the basic industries of the new technological order and the speedy withdrawal of the Russian economy to a new long wave of development of production and productive forces associated with it.